(untitled) (Journal of Plant Disease Sciences, 2017)
The present investigation entitled “Mushroom flora of western ghat of Maharashtra with special reference to spp " was carried out at Plant Pleurotus . Pathology Section, College of Agriculture, Kolhapur. The survey was carried out with object to study biodiversity of mushroom flora in western Maharashtra and to identify mushroom species on the basis of morphological characteristics.Collection of mushroom specimen was conducted during monsoon season of 2015. During the present investigation, seven species of the genus viz., Pleurotus P. ostreatus (2), P. pulmonarius, P. flabellatus, P. porrigens, P. lignatilis P. djamor and were observed in this investigation, the extensive survey of forests and existing places near Kolhapur, Satara, Sindudurg and Pune of Maharashtra was carried out. Identification of mushroom specimen collected was done on the basis of Pleurotus their macroscopic (morphological) and microscopic characters. Pleurotus P. ostreatus, P. show variation among their pileus shape i.e lignatilis, P. pulmonarius, P. flabellatus species had oyster or kidney shape, species showed fan or shell shape, species of oyster mushroom showed tounge P.porrigens shape structure. Other characteristics include form of mushroom i.e single, group or connate (united).Out of those oyster species P. ostreatus, P. pulmonarius, P. flabellatus, P. djamor P. porrigens , are edible but not consumed by people. is Inedible, poisonous so not consumed locally. of mushroom, Pleurotus spp. P.ostreatus P. porrigens had Lilac spore print, had creamish spore print, remaining all 4 species i.e showed white P. pulmonarius, P. flabellatus, P. lignatilis, P. djamor, spore print. The study revealed that macro fungal diversity in the western ghat region of Maharashtra is needs to be conserve properly especially for edible and medicinal purpose.